The Role of Industrial Relations in Enhancing the Productivity of State-Owned Enterprises (SOEs): A Systematic Literature Review - Ibrahim, Saddam Alfayed; Muhammad Farhan; Fitria Awalia Azhari (Program Pascasarjana, Universitas Riau, 2025)
This study aims to systematically review and map various literature findings regarding the role of industrial relations practices in encouraging productivity in Indonesian State-Owned Enterprises (SOEs). Facing the era of business transformation and fierce competition, increasing efficiency and productivity has become an imperative for SOEs. In this context, industrial relations (HR) are identified as one of the most crucial non-technical factors that affect corporate performance. Using the systematic literature review method, this article analyzes scientific publications from the Google Scholar, Sinta, and Scopus databases in the period 2020-2025. The results of the analysis reveal that the role of Industrial Relations (HI) has two contradictory sides. On the one hand, harmonious Industrial Relations (HI) are characterized by constructive social dialogue, trade unions acting as partners, and fair Collective Labor Agreements (PKB), which show a positive correlation with increased employee motivation and operational productivity. On the other hand, Industrial Relations (IP), which is colored by conflict, excessive political intervention, and trade union attitudes towards change, is the main obstacle to productivity. The conclusion of this study is that SOEs need to place Industrial Relations (HI) as a fundamental strategic element, no longer just the fulfillment of formal obligations, to achieve performance excellence